Students’ Experiences in Learning Chemistry at Secondary Schools in Azerbaijan - Farajova, Malak (My University, 2026)
This qualitative study explores how secondary school students experience learning chemistry subject at schools in Baku, Azerbaijan, precisely focusing on the 7th and 8th-grade students. Semi-structured interviews with 16 students and 6 teachers from both public and private schools revealed that students initially perceive chemistry as a “conceptual struggle” because of the abstract disconnection between macroscopic phenomena and symbolic representations, moreover, findings were analyzed in terms of the student engagement framework (Bond et al., 2020), showing that involvement is shaped by three distinct domains: behavioral (driven by laboratory participation, asking questions, and note-taking), affective (influenced by teacher personality, gamified joy, and peer collaboration as emotional support), and cognitive (facilitated by real-world links and everyday metaphors). Additionally, this study also identifies a concept namely “Parallel Learning System”, which happened through factors like AI-assisted explanations, family support, and independent homework that students use to construct meaningful understanding outside the classroom, in order to compensate the challenges of the formal curriculum. Despite the positive drivers for engagement in chemistry learning, a significant gap exists between the national curriculum and actual practice of students, where public school students often remain passive observers during laboratory lessons due to resource constraints. Furthermore, environmental barriers like classroom noise and psychological factors like “chemophobia” significantly diminish affective involvement of students in chemistry lessons. Consequently, this thesis emphasizes the importance of instructional scaffolding and the use of “bridge talk” to help students navigate through Johnstone’s Triangle concept to mitigate fear of chemistry subject, and improve overall scientific literacy.
Keywords: Chemistry Education; Student Engagement; Science Education; Chemistry Learning; Student Perceptions; Laboratory Learning; Cognitive Engagement; Affective Engagement; Curriculum Implementation